Granulysin‐mediated apoptosis of trophoblasts in blighted ovum and missed abortion. (18th May 2018) - Gulic, Tamara; Laskarin, Gordana; Dominovic, Marin; Glavan Gacanin, Lana; Babarović, Emina; Rubesa, Zeljka; Haller, Herman; Rukavina, Daniel
Abstract : Problem: Granulysin (GNLY) is a cytotoxic molecule mostly present in decidual natural killer (NK) cells. Blighted ovum (BO) and missed abortion (MA) represent the early pathological pregnancies with hindered development of the embryoblast or a dead embryo. We investigated the GNLY‐mediated apoptotic mechanism potentially responsible for delayed termination of pregnancy. Method of study: We performed immunohistological and immunofluorescence labeling of decidual tissues (GNLY, Apaf‐1, NF‐κB). NKG2A expression was analyzed by flow cytometry and GNLY mRNA by RT‐qPCR. Results: The GNLY labeling intensity ( H score) was lower in the nuclei of trophoblast cells in BO and MA. GNLY gene levels were inversely detected in BO and MA. A decreased decidual NK cell percentage was found in MA. NK cells from pathological pregnancies expressed lower NKG2A levels. The highest frequency of Apaf‐1 was found in trophoblast cells of MA. NF‐kB was highly expressed in decidual cells of BO. Conclusion: The reduced activation of GNLY‐mediated killing might be implicated in the slower rejection of trophoblast cells in BO and MA. A decreased authentic decidual NK cell number could be responsible for low cytotoxicity against trophoblast cells in MA. In BO, trophoblast cells have a higher survival potential due to increased NF‐kB expression.